Design Optimization and Performance Investigation of a Micro Wind Turbine for Domestic Dwelling Used for Renewable Generation System - Wissam K. Abbas; Majid Abbasalizadeh; Shahram Khalilarya (Energy Science & Engineering)
ABSTRACT This study focuses on wind turbine blade optimization using a MATLAB‐based algorithm, QBlade, and CFD software to improve the performance of micro‐horizontal axis wind turbines (HAWTs) in low wind speed environments, particularly for residential use. The optimization targeted chord length distribution and twist angle to enhance turbine efficiency. The MATLAB algorithm, developed using Blade Element Momentum (BEM) theory, enabled precise aerodynamic performance calculations. Two airfoil profiles, mixed SG6040‐SG6043 and SD7080, were selected based on their performance at low Reynolds numbers of 100,000 and 81,712, respectively, with blades divided into 18 and 19 sections for detailed optimization analysis. Validation was conducted by comparing key aerodynamic parameters, including power coefficients C P and torque, from QBlade and CFD simulations. The results demonstrated excellent agreement, with a relative error of 2.4% for the mixed SG6040‐SG6043 airfoil and less than 1% for SD7080, confirming the reliability and robustness of the methodology. The optimized designs achieved C P values of 0.467 for the mixed SG6040‐SG6043 and 0.45 for SD7080, reflecting substantial performance improvements. This study highlights the effectiveness of combining numerical optimization and high‐fidelity simulations to enhance blade performance. The findings advance HAWT designs, making them efficient and viable for decentralized renewable energy systems in low‐wind speed regions.